Nonlinear Response of Laminated Panels under Blast Load. (2017) - Kumari, Emarti; Singha, M.K.
Abstract: Nonlinear response of laminated composite plates and cylindrical panels subjected to a parabolically distributed blast load is studied here using a shear deformable finite element method. The nonlinear finite element equations of motion are solved in the time domain by an energy and momentum conserving time integration technique. The state-of-stress inside the laminated panels is calculated at each time-step to predict the occurrence of damage using Tsai-Wu quadratic failure criterion. The effects of span-to-thickness ratio, radius-to-span ratio and peak pressure on the nonlinear dynamic response of laminated composite plates and curved panels are investigated.